2013
DOI: 10.1007/s00392-013-0578-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of left ventricular hypertrophy by the R-wave voltage in lead aVL: population-based study

Abstract: We have shown that the simple and single assessment of RaVL presented a greater diagnostic ability in detecting ECHO-LVH in the general population, signaling its value mainly as a screening tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…By using nuclear magnetic resonance as gold standard, Courand et al 28 concluded that the voltage of R wave in aVL lead between 0.5 and 1 mV was a strong indicator of left ventricular hypertrophy. Similarly, Rodrigues et al 29 recognized that the voltage of R wave in aVL lead ≥0.55 mV had good sensitivity (87%) for detecting LVH with preserved specificity (75%). This study showed no positive results of LVH based on R wave voltage (> 1.1 mV) in aVL lead at patients without adverse events, while it was present in 12.5% patients with composite events.…”
Section: Discussionmentioning
confidence: 92%
“…By using nuclear magnetic resonance as gold standard, Courand et al 28 concluded that the voltage of R wave in aVL lead between 0.5 and 1 mV was a strong indicator of left ventricular hypertrophy. Similarly, Rodrigues et al 29 recognized that the voltage of R wave in aVL lead ≥0.55 mV had good sensitivity (87%) for detecting LVH with preserved specificity (75%). This study showed no positive results of LVH based on R wave voltage (> 1.1 mV) in aVL lead at patients without adverse events, while it was present in 12.5% patients with composite events.…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, this threshold was validated in an independent cohort with a slightly different risk profiles, strengthening the validity of our conclusion. In addition, a threshold of 0.6 or 0.55 mV has already been proposed as the best compromise between sensitivity and specificity in detecting LVH by TTE [10,11]. In another study by our group, the optimal RaVL cutoff for detecting cardiac MRI LVH was 0.65 mV [20].…”
Section: Discussionmentioning
confidence: 96%
“…The voltage of R wave in lead aVL (RaVL), a component of the Cornell index, has several advantages: it is simple to measure and reproducible [10] and has been shown more tightly correlated with left ventricular mass (LVM), as assessed by TTE, than Sokolow or Cornell indexes [10,11]. In addition to that, two studies have demonstrated that RaVL predicts major cardiovascular events in hypertensive patients with or without LVH on ECG [10,12].…”
mentioning
confidence: 98%
“…However, the American Electrocardiogram Committee opined: “Published studies are currently insufficient to indicate whether any of the more recently proposed criteria are clearly superior to the others or are simply redundant.” [7] Furthermore, the various ECG criteria have high specificity, but low sensitivity [8]. Consequently, different modifications in the use of ECG have been proposed [9, 10]. With the various uncertainties, the use of ECG can be compromised.…”
Section: Introductionmentioning
confidence: 99%